The Effect of Google Classroom in Blended Learning on University Students’ English Ability - Liya Astarilla Dede Warman (J-SHMIC : Journal of English for Academic, 2021)
This research aimed to investigate Google Classroom's effect on blended learning on university students’ English ability. This research utilized a quasi-experimental design which included experimental and control group design. The study participants comprised 68 students in the first semester at STMIK-AMIK Riau in Pekanbaru-Riau, Indonesia. This research instrument was an achievement test in multiple-choice questions administered to the participants in pre-test and post-test. The quantitative data were collected by using pre-test and post-test to gauge the students’ English ability before and after conducting the treatments in both groups. The finding revealed that statistically, there was a significant difference in the mean score between the experimental and control group in the post-test. The experimental group that learned English through Google Classroom in blended learning achieved a significantly higher score than control group that learned English through the conventional method. It was proved that the t-test was higher than the t-table value (5.270>2.042) at the level of significance 0.05 and p=0.000. This study concluded that blended learning through Google Classroom had contributed to the improvement of students’ English ability.